Elaboration Of Secondary Prevention Measures For Individuals With Cystine Metabolic Disorder To Reduce The Risk Of Urolithiasis : A Critical Review - Dion, Aldy; Christine, Catarina Lilian; Adrianto, Hebert (Jurnal EduHealth, 2024)
Urolithiasis in Asia affects about 1% - 19.1% of the population. Urolithiasis disease in young patients has a significant morbidity rate. Basic metabolic disorder such as cystinuria are often associated with urolithiasis. Cystinuria, a congenital cystine metabolism disorder with an incidence ratio of 1:7,000. Cystinuria is a common condition among urolithiasis patients. The paper aims to summarize recent efforts in secondary prevention to reduce the risk of urolithiasis in cystinuria patients through early detection and prompt treatment. This paper is a narrative review using the literature study method regarding the latest secondary prevention efforts. The library used 24 pieces of literature from research journals and international case reports. Early detection efforts include tracing medical history and urinalysis, followed by an initial diagnosis using PCR, sodium cyanide-nitroprusside test, and attenuated total reflection - fourier transform infrared spectroscopy (ATR-FTIR) can confirm the diagnosis of cystinuria. Thiopronine treatment is currently the main choice, accompanied by a special diet and plenty of water consumption. Another pharmacological therapy (tolvaptan) is still under development and showing promising results. Secondary prevention efforts for cystinuria patients are needed to prevent an adverse urolithiasis event and help reducing morbidity rate.